Anti-SARS-CoV-2 antibodies important in diagnostics of acute hepatitis in children - Pawłowska, Małgorzata; Moppert, Justyna; Sobolewska-Pilarczyk, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2023)
The most common causes of acute hepatitis in children are hepatitis A and autoimmune hepatitis. Hepatitis in the course of Wilson’s disease is sporadically registered in adolescents. An increase of activity of aminotransferases both in the course of multisystem inflammatory syndrome in children (MIS-C) and in the course of COVID-19 has been observed. Hepatitis is common in children with MIS-C and is associated with a more severe presentation and persistent elevation of liver function tests. To date, no cases of acute hepatitis in children due to COVID-19 have been reported. We present 2 cases of acute hepatitis in children where the only cause seems to be a previous asymptomatic SARS-CoV-2 infection.